Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To compare and contrast the piecewise defined functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex], we will examine their behavior in different segments of the domain.
### Definitions:
[tex]\[ f(x)=\left\{ \begin{array}{rl} -x + 2, & x < 0 \\ x^2 + 1, & x > 0 \end{array} \right. \][/tex]
[tex]\[ g(x)=\left\{ \begin{array}{ll} x + 2, & x < 0 \\ x^2 + 2, & x > 0 \end{array} \right. \][/tex]
### Comparisons at Specific Points:
We will evaluate and compare [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] at the points [tex]\( x = -2 \)[/tex], [tex]\( x = -1 \)[/tex], [tex]\( x = 1 \)[/tex], and [tex]\( x = 2 \)[/tex].
1. At [tex]\( x = -2 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(-2) = -(-2) + 2 = 2 + 2 = 4 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(-2) = -2 + 2 = 0 \][/tex]
Thus, at [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = 4 \][/tex]
[tex]\[ g(-2) = 0 \][/tex]
2. At [tex]\( x = -1 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(-1) = -(-1) + 2 = 1 + 2 = 3 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(-1) = -1 + 2 = 1 \][/tex]
Thus, at [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 3 \][/tex]
[tex]\[ g(-1) = 1 \][/tex]
3. At [tex]\( x = 1 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(1) = 1^2 + 1 = 1 + 1 = 2 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(1) = 1^2 + 2 = 1 + 2 = 3 \][/tex]
Thus, at [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2 \][/tex]
[tex]\[ g(1) = 3 \][/tex]
4. At [tex]\( x = 2 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 2^2 + 1 = 4 + 1 = 5 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(2) = 2^2 + 2 = 4 + 2 = 6 \][/tex]
Thus, at [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 5 \][/tex]
[tex]\[ g(2) = 6 \][/tex]
### Summary of Results:
- At [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = 4, \quad g(-2) = 0 \][/tex]
- At [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 3, \quad g(-1) = 1 \][/tex]
- At [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2, \quad g(1) = 3 \][/tex]
- At [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 5, \quad g(2) = 6 \][/tex]
### Comparison and Contrast:
1. For [tex]\( x < 0 \)[/tex]:
- For negative values, both functions are linear.
- [tex]\( f(x) \)[/tex] decreases as [tex]\( x \)[/tex] decreases (i.e., slope = -1), while [tex]\( g(x) \)[/tex] increases as [tex]\( x \)[/tex] decreases (i.e., slope = 1).
- The values of [tex]\( f(x) \)[/tex] are higher than those of [tex]\( g(x) \)[/tex] for the same negative [tex]\( x \)[/tex].
2. For [tex]\( x > 0 \)[/tex]:
- For positive values, both functions are quadratic.
- [tex]\( f(x) = x^2 + 1 \)[/tex] is always less than [tex]\( g(x) = x^2 + 2 \)[/tex] by exactly 1 for any [tex]\( x > 0 \)[/tex].
### Conclusion:
While both [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are piecewise defined functions with linear components for [tex]\( x < 0 \)[/tex] and quadratic components for [tex]\( x > 0 \)[/tex], they differ in both segments of their domain. For [tex]\( x < 0 \)[/tex], [tex]\(f(x)\)[/tex] yields higher values than [tex]\(g(x)\)[/tex]. For [tex]\( x > 0 \)[/tex], [tex]\(g(x)\)[/tex] exceeds [tex]\(f(x)\)[/tex] by a constant difference of 1 unit.
### Definitions:
[tex]\[ f(x)=\left\{ \begin{array}{rl} -x + 2, & x < 0 \\ x^2 + 1, & x > 0 \end{array} \right. \][/tex]
[tex]\[ g(x)=\left\{ \begin{array}{ll} x + 2, & x < 0 \\ x^2 + 2, & x > 0 \end{array} \right. \][/tex]
### Comparisons at Specific Points:
We will evaluate and compare [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] at the points [tex]\( x = -2 \)[/tex], [tex]\( x = -1 \)[/tex], [tex]\( x = 1 \)[/tex], and [tex]\( x = 2 \)[/tex].
1. At [tex]\( x = -2 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(-2) = -(-2) + 2 = 2 + 2 = 4 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(-2) = -2 + 2 = 0 \][/tex]
Thus, at [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = 4 \][/tex]
[tex]\[ g(-2) = 0 \][/tex]
2. At [tex]\( x = -1 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(-1) = -(-1) + 2 = 1 + 2 = 3 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(-1) = -1 + 2 = 1 \][/tex]
Thus, at [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 3 \][/tex]
[tex]\[ g(-1) = 1 \][/tex]
3. At [tex]\( x = 1 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(1) = 1^2 + 1 = 1 + 1 = 2 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(1) = 1^2 + 2 = 1 + 2 = 3 \][/tex]
Thus, at [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2 \][/tex]
[tex]\[ g(1) = 3 \][/tex]
4. At [tex]\( x = 2 \)[/tex]:
- For [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 2^2 + 1 = 4 + 1 = 5 \][/tex]
- For [tex]\( g(x) \)[/tex]:
[tex]\[ g(2) = 2^2 + 2 = 4 + 2 = 6 \][/tex]
Thus, at [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 5 \][/tex]
[tex]\[ g(2) = 6 \][/tex]
### Summary of Results:
- At [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = 4, \quad g(-2) = 0 \][/tex]
- At [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 3, \quad g(-1) = 1 \][/tex]
- At [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2, \quad g(1) = 3 \][/tex]
- At [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 5, \quad g(2) = 6 \][/tex]
### Comparison and Contrast:
1. For [tex]\( x < 0 \)[/tex]:
- For negative values, both functions are linear.
- [tex]\( f(x) \)[/tex] decreases as [tex]\( x \)[/tex] decreases (i.e., slope = -1), while [tex]\( g(x) \)[/tex] increases as [tex]\( x \)[/tex] decreases (i.e., slope = 1).
- The values of [tex]\( f(x) \)[/tex] are higher than those of [tex]\( g(x) \)[/tex] for the same negative [tex]\( x \)[/tex].
2. For [tex]\( x > 0 \)[/tex]:
- For positive values, both functions are quadratic.
- [tex]\( f(x) = x^2 + 1 \)[/tex] is always less than [tex]\( g(x) = x^2 + 2 \)[/tex] by exactly 1 for any [tex]\( x > 0 \)[/tex].
### Conclusion:
While both [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are piecewise defined functions with linear components for [tex]\( x < 0 \)[/tex] and quadratic components for [tex]\( x > 0 \)[/tex], they differ in both segments of their domain. For [tex]\( x < 0 \)[/tex], [tex]\(f(x)\)[/tex] yields higher values than [tex]\(g(x)\)[/tex]. For [tex]\( x > 0 \)[/tex], [tex]\(g(x)\)[/tex] exceeds [tex]\(f(x)\)[/tex] by a constant difference of 1 unit.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.